Sue & Tai-chan. 3 - Konami, Kanata, 1958- (Kodansha Comics, 2021)
"Blissful days abound for Sue and Tai-chan as they settle into a unique, synchronized rhythm. Snooping around for treats, going on fun-filled adventures--they can take on any challenge if they have each other! But when Tai-chan's owner finally returns home, what is a pair of best friends to do...?"--Back cover.